2016
DOI: 10.1021/acs.est.5b03895
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Attenuates the Cytotoxicity and Mutagenicity of PCB 52 via Activation of Genuine Autophagy

Abstract: Graphene oxide (GO), owing to its large surface area and abundance of oxygen-containing functional groups, is emerging as a potential adsorbent for polychlorinated biphenyls (PCBs), which accumulate over time and are harmful to both natural ecosystems and human health. However, the effect of GO against PCB-induced toxicity remains largely unexplored. The present study aimed to investigate the protective effect of GO against PCB 52 induced cytotoxic and genotoxic response in mammalian cells at various exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 50 publications
(80 reference statements)
2
26
1
Order By: Relevance
“…However, the hydrodynamic particle size of GO in PBS and culture medium gradually increased over time than those in water. This indicated that GO was prone to aggregation owing to the highly salted environment and the presence of protein components, which are consistent with the results of previous studies [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…However, the hydrodynamic particle size of GO in PBS and culture medium gradually increased over time than those in water. This indicated that GO was prone to aggregation owing to the highly salted environment and the presence of protein components, which are consistent with the results of previous studies [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…9 Analogously, previous studies also demonstrated that GO actively interacts with cell plasma through the abundant oxygen-containing functional groups on its surface. 69,70 As a result, the association of the flat side with plasma membrane would trigger macrophage activation into the M1 subtype with pro-inflammatory effects. 9,71,72 Different from GO, MoS 2 materials harbored much weaker interaction with plasma membrane, possibly due to the absence of active oxygen-containing functional groups on their surface.…”
Section: Preferential Lung Accumulation Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
“…8 The specic properties of biochar include: a porous structure, large surface area, a variety of mineral components and enriched functional groups, all of which enable it to remove various inorganic or organic contaminants from solutions by absorption, such as heavy metals, mineral salts, phenolic compounds, organic pesticides and PAHs (polycyclic aromatic hydrocarbons). 9,10 Compared with traditional heating, microwave heating possesses the superiority of a rapid heating rate and energy conservation. 11 In addition, biochar produced by microwave irradiation has a larger surface area and more plentiful pore structures than that obtained from traditional heating.…”
Section: -5mentioning
confidence: 99%